PERBANDINGAN KEPEKAAN MODEL MANTEL HAENSZEL DAN MODEL RASCH DALAM MENDETEKSI KEBERBEDAAN FUNGSI BUTIR DITINJAU DARI UKURAN SAMPEL - IDRUS ALWI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
The aims of this research is to study the sensitivity comparison of Mantel Haenszel and Rasch Model for detection differential item functioning, observed from the sample size. These two differential item functioning (DIF) methods were compared using simulate binary item respon data sets of varying sample size, 200 and 400 examinees were used in the analyses, a detection method of differential item functioning (DIF) based on gender difference. These test conditions were replication 4 times. For both differential item functioning (DIF) detection methods, a test length of 42 items was sufficient for satisfactory differential item functioning (DIF) detection with detection rate increasing as sample size increased. Finding the study revealed that the empirical result show Rasch Model are more sensitive to detection differential item functioning (DIF) than Mantel Haenszel. With reference to findings of this study, it is recomended that the use of Rasch Model in evaluation activities with multiple choice test. For this purpose, it is necessary for every school to have some teachers who are skillfull in analyzing results of test using modern methods (Item Response Theory).